Yerevan physics institute steps towards an LHC computing Grid - Karen S. Mkoyan (Изд-во НАН РА)
The main goal of this paper is to develop a User Interface (UI) for scientists from Yerevan Physics Institute to have access to LCG infrastructure. The structure and mechanisms of the suggested interface, which uses DESY Grid site for accessing to LHC Grid are given.
Keywords: Physics; Mathematics